Kisújszállás, ‘the Cultural Capital of Great Cumania’ – Shrinkage, Resilience and Culture-Based Urban Development in East Hungary - Tibor Kovács (DETUROPE)
Demographic changes (population decline) and their (urban) consequences are a real challenge for the small and medium-sized towns of Europe and Hungary. The research question concerning this phenomenon is: how to deal with urban shrinkage and is there any proper and overall answer to this process? Although there is no universal cure for the maintenance and development of these towns, nor for stopping demographic shrinkage, resilience and local culture can provide good conditions to deal with the urban issues raised. Kisújszállás, the cultural capital of Great Cumania can be a good example of how the function-extending renewal of a historical building of the town can strengthen its retaining power and how it can also contribute to increasing the attractiveness of the settlement, all in all, making it a more attractive and viable place to live in.